Comparison of moment-angle profile of elbow flexors extensors in elite young overhead athletes - Nikolaidou, M. E.; Boudolos, K. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
In in-vivo conditions, the moment vs. joint angle curve (M-A profile) is typically used to examine the force-length characteristics of muscles. During attack in volleyball (VB) and water-polo (WP), the elbow moves through an arc of 60°-70° joint flexion suggesting that the flexor and extensor muscles operate in similar joint configurations, therefore muscle lengths. Previous studies (Herzog et al., 1991) have shown different extensor moment-knee angle relations between different athletes that were attributed to adaptation of muscle function to different functional requirements. The purpose of this study was to compare the moment-elbow angle profile between elite young overhead athletes.